2008
DOI: 10.1086/592350
|View full text |Cite
|
Sign up to set email alerts
|

Precursors in Swift Gamma Ray Bursts with Redshift

Abstract: We study a sample of gamma-ray bursts detected by the Swift satellite with known redshift which show a precursor in the Swift BAT light curve. We analyze the spectra of the precursors and compare them with the time-integrated spectra of the prompt emission. We find neither a correlation between the two slopes nor a tendency for the precursors spectra to be systematically harder or softer than the prompt ones. The energetics of the precursors are large: on average, they are just a factor of a few less energetic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
118
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 21 publications
(18 reference statements)
2
118
0
Order By: Relevance
“…If this process is related to a delayed reactivation of the central engine, this could produce an observable signature at higher frequencies around the new t 0,2 . The existence of prompt GRB light-curves showing long periods of quiescence between separate peaks lasting up to a few hundreds seconds has already been discussed in the literature (Ramirez-Ruiz et al 2001;Romano et al 2006;Burlon et al 2008Burlon et al , 2009Gruber et al 2010). Most of them are precursors (i.e., peaks preceding the main GRB event), but Burlon et al (2008) report on the case of GRB 060210 where two postcursors are observed 60 and 150 s after the end of the main burst.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…If this process is related to a delayed reactivation of the central engine, this could produce an observable signature at higher frequencies around the new t 0,2 . The existence of prompt GRB light-curves showing long periods of quiescence between separate peaks lasting up to a few hundreds seconds has already been discussed in the literature (Ramirez-Ruiz et al 2001;Romano et al 2006;Burlon et al 2008Burlon et al , 2009Gruber et al 2010). Most of them are precursors (i.e., peaks preceding the main GRB event), but Burlon et al (2008) report on the case of GRB 060210 where two postcursors are observed 60 and 150 s after the end of the main burst.…”
Section: Discussionmentioning
confidence: 84%
“…The existence of prompt GRB light-curves showing long periods of quiescence between separate peaks lasting up to a few hundreds seconds has already been discussed in the literature (Ramirez-Ruiz et al 2001;Romano et al 2006;Burlon et al 2008Burlon et al , 2009Gruber et al 2010). Most of them are precursors (i.e., peaks preceding the main GRB event), but Burlon et al (2008) report on the case of GRB 060210 where two postcursors are observed 60 and 150 s after the end of the main burst. There is no clear example with later time (t ≥ 1500 s) post-cursors, although faint late-time peaks are hardly detectable by BAT (see Holland et al 2010, for a possible candidate).…”
Section: Discussionmentioning
confidence: 84%
“…Burlon et al 2008, and references therein). Episodes 1 and 2 are not temporally separated by a quiescent time.…”
Section: Discussionmentioning
confidence: 99%
“…From the observational point of view, long periods of quiescence of the central engine, lasting up to thousands of seconds, have been observed in a fraction of GRBs showing the so called pre-or post-cursors in their prompt gamma-ray emission phase (Ramirez-Ruiz et al 2001;Romano et al 2006;Burlon et al 2008Burlon et al , 2009Gruber et al 2010). If these gamma-ray emission episodes are associated with the acceleration of different shells with respect to the main prompt event, these are supposed to interact with the latter ones, probably leading to an observable optical flux rebrightening if the difference in Γ is large enough.…”
Section: Ultrarelativistic Shell Collisionmentioning
confidence: 99%